1994
DOI: 10.1002/ajp.1350340106
|View full text |Cite
|
Sign up to set email alerts
|

Interovarian communication for the control of follicular growth and corpus luteum function in the cebus monkey

Abstract: We have investigated the role of the utero-ovarian ligament (UOL) in the alternating ovulatory performance of the ovaries in the capuchin monkey. In intact animals, the ovulation rate was near 90%, with 67.5% of ovulations occurring in the left ovary. Sectioning the UOL in any phase of the cycle decreased the ovulation rate by 40%, and restricted ovulations to the ovary still connected to the uterus by the UOL. Estradiol and progesterone levels were significantly reduced throughout the following cycles in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Contrary to studies conducted in the capuchin monkey and in women , we did not find any difference in the ovulation rate between left and right ovaries, suggesting that both ovaries have a similar activity rate in owl monkeys.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to studies conducted in the capuchin monkey and in women , we did not find any difference in the ovulation rate between left and right ovaries, suggesting that both ovaries have a similar activity rate in owl monkeys.…”
Section: Discussioncontrasting
confidence: 99%
“…In C. apella, a great number of follicles in the right ovary can suggest a lower functionality of this compared to the left ovary. Nagle et al (1994) showed that the ovulation rate in the left ovary is 62.5% and 37.5% for the right ovary in the C. apella. In this study, the follicular ovarian population was found, without verifying the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…These later authors studied the ovaries of four adult Sapajus apella females, and recorded more follicles present in the right ovary than in the left one (Domingues et al , 2004). They suggested that in S. apella the right ovary has more follicles because it is less functional than the left one, since Nagle et al (1994) observed the lowest ovulation rates in the right ovaries S. apella. In women, however, no differences in ovulation rates are observed between right and left ovaries (Lass et al , 1997), although some authors describe a more frequent ovulation rate in the right ovary (Potashnik et al , 1987; Fukuda et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lopes et al since Nagle et al (1994) observed the lowest ovulation rates in the right ovaries S. apella. In women, however, no differences in ovulation rates are observed between right and left ovaries (Lass et al, 1997), although some authors describe a more frequent ovulation rate in the right ovary (Potashnik et al, 1987;Fukuda et al, 2000).…”
mentioning
confidence: 92%